2023
DOI: 10.3390/jintelligence11020029
|View full text |Cite
|
Sign up to set email alerts
|

Can Intelligence Affect Alcohol-, Smoking-, and Physical Activity-Related Behaviors? A Mendelian Randomization Study

Abstract: People with high levels of intelligence are more aware of risk factors, therefore choosing a healthier lifestyle. This assumption seems reasonable, but is it true? Previous studies appear to agree and disagree. To cope with the uncertainty, we designed a mendelian randomization (MR) study to examine the causal effects of genetically proxied intelligence on alcohol-, smoking-, and physical activity (PA)-related behaviors. We obtained genome-wide association study (GWAS) datasets concerning these variables from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 84 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…For the identification and correction of horizontal pleiotropy, we utilized the Mendelian Randomization Pleiotropy RESidual Sum and Outlier (MR-PRESSO) test to detect and remove outliers. Furthermore, to ascertain the robustness of each IV, we calculated the F-statistic (β 2 /se 2 ) for every IV ( Li et al, 2023 ), excluding any with an F-statistic less than 10. This process helped ensure the reliability of our IVs, thereby strengthening the validity of our MR analysis findings ( Burgess and Thompson, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…For the identification and correction of horizontal pleiotropy, we utilized the Mendelian Randomization Pleiotropy RESidual Sum and Outlier (MR-PRESSO) test to detect and remove outliers. Furthermore, to ascertain the robustness of each IV, we calculated the F-statistic (β 2 /se 2 ) for every IV ( Li et al, 2023 ), excluding any with an F-statistic less than 10. This process helped ensure the reliability of our IVs, thereby strengthening the validity of our MR analysis findings ( Burgess and Thompson, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although research in this area has primarily been concerned with socioeconomic success and has relied on variables such as income or educational attainment as dependent variables, there have been quite a few papers about the relationship between these variables and other life outcomes such as happiness ( DeNeve and Cooper 1998 ; Nikolaev and Salahodjaev 2016 ), religiosity ( Kanazawa 2010 ), risk taking ( Gladden et al 2009 ) or marital success ( Gonzaga et al 2010 ). The current Special Issue also provides rich and illuminating examples of life outcomes which are not often studied in intelligence and personality research, such as anti-social behavior ( O’Connell ( 2023 ), which also studies risky behavior), alcohol consumption, smoking and physical activity ( Li et al 2023 ), as well as scientific creativity ( McGregor and Frodsham 2023 ).…”
Section: Challenge 3: What Are “Important Life Outcomes”?mentioning
confidence: 99%
“…The most well-studied traits include cognitive functioning and educational attainment, structural brain measures, and psychiatric disorders (predominantly MDD, PTSD, ADHD). For alcohol use disorder, there is consistent evidence that higher intelligence and educational attainment causally decrease the risk of developing AUD [9,96,97]. One study indicated that PAU liability, which combined AUD and problematic drinking, may also causally decrease educational attainment [9], however other studies have failed to replicate this finding [97].…”
Section: Causes and Consequences Of Substance Use Disordersmentioning
confidence: 99%
“…Higher intelligence may decrease the odds of nicotine dependence [96] and nicotine dependence increases the risk of schizophrenia (even when corrected for CUD) [111]. There is no clear evidence for causal effects between nicotine dependence and ADHD [114], nor from nicotine dependence to suicide [106].…”
Section: Causes and Consequences Of Substance Use Disordersmentioning
confidence: 99%